Bismuth telluride functionalized bismuth oxychloride used for enhancing antibacterial activity and wound healing efficacy with sunlight irradiation. (10th December 2021) - Chen, Rui; Wei, Liqi; Yan, Yan; Chen, Guoli; Yang, Xiaodong; Liu, Yang; Zhang, Mengyuan; Liu, Xin; Cheng, Yan; Sun, Jun; Wang, Lili
Abstract : Bismuth telluride was used to narrow the bandgap of bismuth oxychloride nanosheets to effectively produce reactive oxygen species, exhibit excellent bacterial inactivation and promote wound healing abilities. Abstract : Bacterial infection can lead to chronic non-healing wounds and serious tissue damage. The wound healing process could be accelerated through bacterial inactivation using some semiconductor nanomaterials with the irradiation of light. Herein, we develop sunlight triggered bismuth telluride-bismuth oxychloride heterostructure nanosheets as antibacterial agents for promoting wound healing, in which bismuth telluride can effectively narrow the bandgap of bismuth oxychloride, resulting in more sunlight absorption and higher antibacterial activity. In fact, the bandgap of bismuth oxychloride has been narrowed from 3.25 eV to 2.37 eV as proved by ultraviolet-visible diffuse reflectance spectroscopy. With simulated sunlight irradiation, bismuth telluride-bismuth oxychloride nanosheets could effectively produce reactive oxygen species and inhibit the growth of both Gram-positive and Gram-negative bacteria. In vivo experiments further confirmed the excellent wound healing capability of bismuth telluride-bismuth oxychloride nanosheets. This work may provide a facile strategy for designing sunlight triggered bacterial inactivation agents.